PENGARUH PROFITABILITY DAN INVESTMENT OPPORTUNITY SET TERHADAP KEBIJAKAN DIVIDEN TUNAI DENGAN LIKUIDITAS SEBAGAI VARIABEL PENGUAT - Janrosl, Viola Syukrina E (Jurnal Ekobistek, 2016)
The purpose of this study is to investigate, test and prove the effect of profitability, investmen opportunity, and liquidity of the cash dividend policy in companies listed on the Indonesia Stock Exchange (IDX) in 2009 to 2011. The sample used in this study were 10 companies. Multiple regression analysis and hypothesis testing using the t test used in this study to test the partial regression coefficients and F test to test the significance of the effect together with the level of significance of 5%. It also performed classical assumption that including normality test, multicollinearity test, test and test heterokedastisitas autocorrelation. In the classical assumption test results showed that there were no irregularities classical assumptions, it is shown that the available data has been qualified to use multiple linear regression models. Results showed investment opportunity has a significant leverage on dividend policy as indicated by the significant level of investment opportunity for the variabel 0,00<0,05,and Other variables in this study, namely profitability and liquidity have no significant effect on dividend policy, in show the significant level of 0,204>0,05 and for variabel 0,158>0,05 liquidity simultaneously or jointly variable profitability, investment opportunity and liquidity have a significant influence on dividend policy. Finally, the author suggests to investors in the Indonesia Stock Exchange for more attention to the information released by the company in making the decision to invest. Keywords :       Profitability Ratios, Investment Opportunity, Liquidity and  Dividend Policy.